Functional Feasibility in Optimal Evaluation of Water Distribution Network Performances - Fuso, Flavia (2020)
The traditional approach for the optimization of water distribution networks (WDNs) does not always lead to consistent solutions from an operational point of view. The latest optimization algorithms identify solutions that are “the best solutions” in mathematical terms but that can be less than robust against changes in operating conditions, resulting in the worst case in hydraulically infeasible configurations. Thus, this paper aims to provide a methodology that can synthesize the network performance capabilities under the change in operating conditions with two convergent strategies. The first consists of the implementation of new performance indices (PIs), the demand deficit and the pressure range, and the evaluation of their ability to criticality highlight in operating conditions. The second is the introduction of a new approach to weight the infeasible solutions in the final result, which are those inconsistent with the real hydraulic network performances. The analysis shows that the use of these new indices makes it easier to understand the behavior of the network and to identify any weaknesses. This is true if these indices consider the hydraulically inconsistent solutions that may arise from the simulations of di erent operation conditions; otherwise, results that poorly represent the real behavior of the network would be obtained.